Adjusting approaches of basal texture for improvement of tension-compression asymmetry in extruded magnesium alloys. Issue 7 (3rd July 2023) - Chen, Wenzhen; Wu, Wenjie; Wang, Wenke; Zhang, Wencong; Liu, Xinhua; Kim, Hyoung Seop
ABSTRACT: Texture adjusting approaches of divergence, inclination, and deviation were proposed to improve the tension-compression asymmetry in magnesium alloys. The dominant deformation mechanism during tensile and compressive yielding was quantified based on the Sachs assumption and primarily manifested as the extent of twinning inhibition and the transition between twinning and slip with the variation of texture adjustment. Its impacts on associated yield strength and asymmetry were estimated by the modified Hall-Petch relationship. Slight texture adjustments, particularly of basal texture divergence, can significantly improve the strength asymmetry while avoiding severe strength loss, illustrating the significance and potential of texture adjustment in engineering. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: Yield strength and the contribution of deformation mechanisms were predicted using the modified Hall-Petch relationship, and texture adjustment strategies were further established to improve tension-compression asymmetry.